2019
DOI: 10.3390/rs11091034
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling between Precipitation Processes and Mountain Wave Induced Circulations Observed with a Vertically Pointing K-Band Doppler Radar

Abstract: Recent studies reported that precipitation and mountain waves induced low tropospheric level circulations may be decoupled or masked by greater spatial scale variability despite generally there is a connection between microphysical processes of precipitation and mountain driven air flows. In this paper we analyse two periods of a winter storm in the Eastern Pyrenees mountain range (NE Spain) with different mountain wave induced circulations and low-level turbulence as revealed by Micro Rain Radar (MRR), microw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Common methods for distinguishing precipitation types include using Formvar slides to collect particles and manually determine the types with a microscope [10,[39][40][41] or automatically judging the precipitation particle pictures taken by combining with an image recognition algorithm [7,12]. In addition, because the V-D relationships between different types of precipitation are obviously different, the V-D function fitted by 1-min average data can also be used to distinguish precipitation types [11,42,43]. In this study, the Vfit = aD b relationship fitted with a 1-min sample (using the least square method) was matched with the 15 V-D relationships in Table 2, and the type with the smallest difference was considered to be the type of the 1-min sample 32 32 2 3 1arg min ( ( ) ( ))…”
Section: Classification Of Precipitation Typesmentioning
confidence: 99%
“…Common methods for distinguishing precipitation types include using Formvar slides to collect particles and manually determine the types with a microscope [10,[39][40][41] or automatically judging the precipitation particle pictures taken by combining with an image recognition algorithm [7,12]. In addition, because the V-D relationships between different types of precipitation are obviously different, the V-D function fitted by 1-min average data can also be used to distinguish precipitation types [11,42,43]. In this study, the Vfit = aD b relationship fitted with a 1-min sample (using the least square method) was matched with the 15 V-D relationships in Table 2, and the type with the smallest difference was considered to be the type of the 1-min sample 32 32 2 3 1arg min ( ( ) ( ))…”
Section: Classification Of Precipitation Typesmentioning
confidence: 99%
“…For the whole period, the MESO and LES simulations reproduce the daily cycle of the TKE and reproduce the turbulence intensity changes through time. Although the correlation is very good at all levels (Table 5), MESO simulation, as expected, is not able to capture the observed turbulence peaks, while LES approximates better the enhanced TKE periods (18,22,28 June and 3 of July) but generally underestimating the turbulence intensity. These days correspond to non-IOP periods, when large scale winds from W and N dominated the region.…”
Section: Model Performance: Turbulent Quantitiesmentioning
confidence: 55%
“…Many other studies have used real case LES to simulate atmospheric flows in complex terrain areas [20][21][22] where grid sizes of few hundreds of metres are needed to resolve the terrain elevation and LES approximation is required. Other authors suggested the need to use LES to resolve small-scale turbulent processes in complex terrain such as downslope windstorms [23], low-level turbulence and rotors [24,25], precipitation dynamics [26][27][28][29] or other small scale processes. Recently, the authors of [30,31] used WRF-LES with domains nested within mesoscale domains and examined the resulting flow field.…”
Section: Introductionmentioning
confidence: 99%
“…The location is a relatively wide valley oriented west to east, with limited radar coverage due to orographic beam blockage (Bech et al [40], Trapero et al [41]) so most of the MRR beam cannot be directly compared with existing ground-based weather radar observations. The Cerdanya-2017 field campaign aimed at studying various complex terrain phenomena, including cold pool formation, mountain waves and orographic precipitation-see Gonzalez et al [17]; Udina et al [42] for more details.…”
Section: Instruments and Site Descriptionmentioning
confidence: 99%